Financial reporting and macroeconomics - Trombetta, Marco (Taylor & Francis, 2021)
Financial Reporting (FR) is a fundamental source of information for the correct functioning of markets. Traditionally, FR is associated with the communication activity done by firms to inform stakeholders and the general public about their financial performance. In the first and second part of this essay I revisit some of the channels through which firm-level FR affects and is affected by the macroeconomic environment. However, companies are not the only economic actors that engage in a FR activity. Local and national governments produce financial reports as well. In the third part of this essay, I review how we can use the theoretical framework developed for firm-level FR to study government-level FR. I conclude by highlighting the importance of incentives as the fundamental mediator of the relationship between FR and Macroeconomics. I remark how they shape different FR environments during crisis and non-crisis periods and the importance of taking these differences into account while regulating and supervising markets.
Keywords: financial reporting;accounting regulation;crisis;fiscal guidance; financial reporting; accounting regulation; crisis; fiscal guidance; 53 Ciencias Económicas::5309 Organización de la industrial y política económica pública::5309.04 Estructura del mercado; ODS 16 - Paz, justicia e instituciones sólidas